1994
DOI: 10.1902/jop.1994.65.12.1097
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies on Laser Scaling of Subgingival Calculus With an Erbium:YAG Laser

Abstract: The effectiveness of a newly‐developed Er:YAG laser with a fiber delivery system to remove subgingival calculus was examined in vitro. Fifty‐three (53) periodontallyinvolved human extracted teeth with a band of subgingival calculus were used. Two experiments were conducted: in experiment 1, laser scaling was performed with water irrigation on a straight line and on a broad area, against the subgingival calculus at the energy levels of 10 to 120 mJ/pulse (3.5 to 42.4 J/cm2/pulse) and the pulse repetition rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
219
1
17

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(246 citation statements)
references
References 37 publications
(13 reference statements)
9
219
1
17
Order By: Relevance
“…As a result, dentin temperature might have been raised higher than 60 a temperature at which collagen transforms from highly ordered helices to amorphous gelatin 26) . Previous research work 27) showed that using of Er:YAG laser with parameters of 30 mJ/pulse and 10 pps the root temperature increased under dry condition to 66.5 , while that under wet condition remained at 28.6 . Moreover, it was reported that the calcified collagen molecules in dentin might break down at approximately 175 , however changes in collagen structure, which might occur with such heating and dehydration, can be reverted to natural conformation after rehydration provided that the surface temperature did not increase beyond 175 28) .…”
Section: Discussionmentioning
confidence: 92%
“…As a result, dentin temperature might have been raised higher than 60 a temperature at which collagen transforms from highly ordered helices to amorphous gelatin 26) . Previous research work 27) showed that using of Er:YAG laser with parameters of 30 mJ/pulse and 10 pps the root temperature increased under dry condition to 66.5 , while that under wet condition remained at 28.6 . Moreover, it was reported that the calcified collagen molecules in dentin might break down at approximately 175 , however changes in collagen structure, which might occur with such heating and dehydration, can be reverted to natural conformation after rehydration provided that the surface temperature did not increase beyond 175 28) .…”
Section: Discussionmentioning
confidence: 92%
“…The denatured dentin irradiated by an Er:YAG laser beam has a similar structure to that of dentin heattreated at 500°C and 800°C and analyzed by XRD analysis 20) . The root temperature was elevated to 66.5°C when subjected to Er:YAG laser irradiation with a pulse energy of 30 mJ at a repetition rate of 10 Hz under dry conditions, while under wet conditions it was elevated to 28.6°C 33) . Changes in the components of dentin are not expected to occur at these temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Er:YAG laser to remove subgingival dental calculus has already been shown in in vitro studies (Aoki et al, 1994;Folcwaczny et al,2000;Frentzen et al, 2002). In 1994 Aoki et al first documented the capacity of Er:YAG laser to remove dental calculus in an in vitro study, using a pulsed mode under irrigation.…”
Section: Periodontal Applications Of Er:yag Lasermentioning
confidence: 99%
“…The calculus was completely removed without thermal change of the root surface. Aoki et al (1994) evaluated the effectiveness of Er:YAG laser compared to conventional ultrasonic scaling. The panel set was 40 mJ/pulse (14.2 J/cm 2 per pulse) and 10 Hz with water spray using a conventional tip at 30° to the root surface.…”
Section: Periodontal Applications Of Er:yag Lasermentioning
confidence: 99%